Que nossas vistas se voltem para os ônibus: a implantação dos auto-omnibus em Fortaleza (1926-1953) - Silva, Ana Carla Pereira da (2016)
Used by most of the population, the public transport bus service is a striking element in Fortaleza’s quotidian nowadays. The importance of this vehicle in Fortaleza, however, was being built over time. This research investigates the bus deployment process in Fortaleza over the years 1926 and 1953. The year 1926 marks the time of the appearance of the first private transport bus company, Matadouro Modelo, very important project for widespread use of these vehicles in the city. The year of 1953 refers to the time of approval of a set of laws that provided for the restructuring of the public transport service in the city. Based on the analysis of sources such as local newspapers, urbanization plans, minutes of City Hall, criminal cases, statistical book, this research makes it possible to understand the implications of the introduction of this technical object in the city and the daily lives of its citizens. It also allows to understand how, amid attempts to build a modern Fortaleza, the buses were affected by the intervention of public policies in the urban space. Investigating this modality of transport can therefore contribute to a better understanding of the role of the bus in Fortaleza nowadays, in order to deconstruct its dominance.